2020
DOI: 10.3390/e22101070
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis on the Blood Flow through Anisotropically Tapered Arteries Filled with Magnetic Zinc-Oxide (ZnO) Nanoparticles

Abstract: The present analysis deals with the entropy analysis of the blood flow through an anisotropically tapered arteries under the suspension of magnetic Zinc-oxide (ZnO) nanoparticles (NPs). The Jeffrey fluid model is contemplated as blood that is electrically conducting and incompressible. The lubrication approach is used for the mathematical modeling. The second law of thermodynamics is used to examine the entropy generation. The exact solutions are obtained against velocity and temperature profile with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…Authors of references [33][34][35] also utilized Laplace transformation and Riemann-sum approximation (RSA) in treatment of the governing equations. Relevant articles relating to the study may be found in references [36][37][38][39][40][41].…”
mentioning
confidence: 99%
“…Authors of references [33][34][35] also utilized Laplace transformation and Riemann-sum approximation (RSA) in treatment of the governing equations. Relevant articles relating to the study may be found in references [36][37][38][39][40][41].…”
mentioning
confidence: 99%
“…the peristaltic motion of non-Newtonian fluid with heat and mass transfer under the effect of a magnetic field through a porous medium is discussed by El-Dabe et al [18]. Zhang et al [19] discussed the entropy analysis of prestaltic blood flow through an anisotropically tapered arteries with suspened magnetic Zinc-oxide (ZnO). The blood is considered to obey Jeffrey fluid model under the effect of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Some major studies on the nanoparticles with blood flow are given in refs. [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%